A Standing Invitation to the Gods: Philosophy of Religion and the Phenomenology of the Sacred - Nordlander, Andreas (Religions, 2024)
Does philosophy of religion, specifically, have anything to contribute to the cultural debate about the modern crisis of meaning, and particularly to attempts at retrieving a sense of enchantment beyond human construction? Suggesting a methodological rapprochement between philosophy of religion and phenomenology, I explore a recent popular attempt to reenchant the world through a retrieval of the sacred: All Things Shining: Reading the Western Classics to Find Meaning in a Secular Age (2011) by Hubert Dreyfus and Sean Dorrance Kelly. Using their work as a foil, I discuss the relation between phenomenology and metaphysics in the experience of the sacred, specifically the possibility of a pluralism that is nonetheless realist; the necessity of social embeddedness and pedagogy in the constitution of sacred meaning; and finally, the problem of moral discrimination within this sphere. Through this critical discussion a constructive argument emerges: philosophy of religion done in a phenomenological mode has resources to address these difficult issues, and thus to explore experiences of the sacred in ways that are metaphysically sophisticated, attentive to historical tradition and pedagogy in the constitution of meaning, as well as to the need of communal moral deliberation in the sphere of the sacred.